Vaginal culture for IVF allows two mothers to carry the same pregnancy: Is more always better? - Babcock Gilbert, Sara (Case Rep Womens Health, 2019)
• Intravaginal culture (IVC) is not a new technology but is gaining in popularity; • The INVOcell device is marketed as a lower cost treatment option to in-vitro fertilization (IVF); • Previous studies done by the INVOcell owned company have shown similar live birth rates between INVOcell IVC and IVF; • It is unclear how much of a cost savings is present with use of IVC compared to traditional IVF; • IVC may represent a viable option for fertility treatment in select patients.